The Effectiveness of Using the SOLO Taxonomy in Acquiring Students the Concepts of Coordinate Geometry - Mohammad A. Ghunaimat; Esraa Ahmed Alawneh (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: The study aimed to investigate the effect of using the SOLO taxonomy levels on Prince Faisal Technical College students' acquisition of coordinate geometry concepts. To achieve the study's objective, Method: The researcher developed a test of acquisition of coordinate geometry concepts. The study used the semi-experimental approach with a pre-post design, and it was applied to (51) students from the college, who were divided into two groups: one experimental (25) student studied using the SOLO taxonomy levels, and the other controlled (26) students studied in the usual way. Results showed a positive effect of using the SOLO taxonomy as a strategy for teaching mathematics, especially in students' acquisition of concepts of coordinate geometry. The study recommended using the SOLO Taxonomy levels on students' acquisition of mathematical concepts in other fields such as algebra, statistics, etc. Novelty: This research presents novelty through the use of Solo taxonomy levels of classification in teaching mathematics, designing a teaching strategy to enable students to acquire concepts of coordinate geometry so that it is easy for teachers to implement this strategy in teaching mathematics.